Cervical Cancer Risk Factors at Haji Adam Malik General Hospital Medan 2016-2018 - Fikar Siregar, Muhammad Khairi Akbar; Rivany, Riza (Sumatera Medical Journal, 2021)
The incidence of cervical cancer is still quite high. It is never separated from the risk factors that influence it. Some of them are sexually active, relatively young marital age, have high parity, use of contraception, and smoking can increase a woman's potential for cervical cancer. The aim of this study was to determine the characteristics of patients about the risk factors for cervical cancer in Haji Adam Malik General Hospital, Medan in 2016-2018. This research method uses descriptive observational design with cross sectional using medical record data. The results of this study using consecutive sampling techniques, took 100 samples and obtained several characteristics are age of patients, age of marriage, marriage history, number of parities, use of contraception, and smoking history. From this study it can be concluded that the characteristics of the incidence of cervical cancer in the General Hospital of Haji Adam Malik Medan in 2016-2018 are 50-59 years old, marital age ≤ 20 years old, married once, multigravida, uses injection type of hormonal contraception , and not smoking .